Previsão da geração de resíduos sólidos urbanos para o aterro sanitário no município de Campina Grande - PB - Cezário, Janaína Aparecida (2022)
The prediction of the generation of urban solid waste is of fundamental importance for the urban planning process in the volume of solid waste produced in the municipalities and how this whole process helps the environment. The estimate serves as a basis for infrastructure adequacy, sustainable development, optimization of resources used in the treatment of these solid wasteand that its disposal is adequate and has a good waste management. A system to be effective requires a forecasting model that is appropriate and meets the needs that are intended from its planning to its execution. This study was carried out using time series to predict the generation of urban solid waste disposed of in the landfill in Campina Grande, located in the state of Paraíba. For the understanding and analysis of the behavior of the data, descriptive statistics techniques were used and thus adjusted the model with the time series techniques. The best fit model is the Sarima (1,0,0)(1,1,0){12} due to meeting all the assumptions that are necessary to obtain a good model. The forecast designed an increase in the generation of solid waste produced and disposed of in the landfill by August 2022. The per capita generation of municipalities and the coverage rate of urban solid waste collection is calculated based on official data from the Brazilian Institute of Geography and Statistics (IBGE), as well as the National Sanitation Information System (SNIS) in addition to the database under study, and the indicators for municipalities that dispose of their solid waste in the landfill in Campina Grande are presented. The modeling of urban solid waste can help in decision making, collection management, programs to encourage selective collection, and contribute positively to the control of environmental impacts.